Peran Employee Green Behavior Sebagai Bentuk Mediasi Peningkatan Employee Engagement Terhadap Sustainability Organisasi - Aisah, Siti Nur (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2025)
This study aims to examine the mediating role of employee green behavior in the relationship between employee engagement and organizational sustainability. The research background is based on the importance of implementing environmentally friendly practices in the workplace as part of an organizational sustainability strategy, where employee engagement potentially enhances green behavior that impacts sustainability performance. A quantitative approach with a survey method was employed, targeting employees of PT. Tapian Nadenggan Tbk., which has implemented the ISO 14001 environmental management system. Data were collected using a 36-item questionnaire and analyzed through Partial Least Squares (PLS). The findings reveal that employee engagement has a significant effect on organizational sustainability (β = 0.469; p < 0.05) as well as on employee green behavior, which in turn significantly mediates this relationship (β = 0.480; p < 0.05). The R² results indicate that employee engagement contributes 27.3% to the formation of employee green behavior and, together with employee green behavior, explains 65.7% of the variance in organizational sustainability. These results highlight that employee involvement in environmentally friendly practices strengthens organizational sustainability performance. The practical implication suggests that organizations should integrate sustainability values into their work culture to achieve long-term sustainable performance.